The Effect of Restaurant Atmosphere on Customer Satisfaction and The Effect of Customer Satisfaction on Repurchase Intention at Amber Resort Lombok Restaurant - Saputra, Hendri Yadi (Jurnal Internasional Riset Bisnis Pariwisata, 2023)
This study aims to determine the effect of restaurant atmosphere on customer satisfaction and Repurchase Intention at Amber Lombok Beach Resort, Data collection in this study used questionnaires distributed directly to guests, and was also carried out by directing respondents to an online questionnaire by providing a google form link on the device provided by the researcher. This study includes variables of comfort level, restaurant scenery, restaurant appearance, consumer satisfaction, and repurchase intentions. The analysis used to test the validity and reliability of the questionnaire and test the hypothesis in this study used SPSS and Smart PLS. The results showed that the restaurant atmosphere consisting of comfort level, restaurant scenery, and restaurant appearance has a significant effect on customer satisfaction, as well as for the variable customer satisfaction has a significant effect on repurchase intentions.